2008
DOI: 10.1007/978-3-540-76280-5_14
|View full text |Cite
|
Sign up to set email alerts
|

Review of Classifier Combination Methods

Abstract: Classifier combination methods have proved to be an effective tool to increase the performance of pattern recognition applications. In this chapter we review and categorize major advancements in this field. Despite a significant number of publications describing successful classifier combination implementations, the theoretical basis is still missing and achieved improvements are inconsistent. By introducing different categories of classifier combinations in this review we attempt to put forward more specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
102
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(106 citation statements)
references
References 53 publications
(67 reference statements)
2
102
0
2
Order By: Relevance
“…The goal of combining classifiers is to conceive a more efficient one which operates on the same data as the base classifiers and separates the same type of classes [21]. As stated in [21] if we denote the score assigned to the class i, by the classifier j : Sij , Therefore, a combination rule is a function f , and the final combination of the scores of the class i is in (3):…”
Section: Combination Of Classifiersmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of combining classifiers is to conceive a more efficient one which operates on the same data as the base classifiers and separates the same type of classes [21]. As stated in [21] if we denote the score assigned to the class i, by the classifier j : Sij , Therefore, a combination rule is a function f , and the final combination of the scores of the class i is in (3):…”
Section: Combination Of Classifiersmentioning
confidence: 99%
“…As stated in [21] if we denote the score assigned to the class i, by the classifier j : Sij , Therefore, a combination rule is a function f , and the final combination of the scores of the class i is in (3):…”
Section: Combination Of Classifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical and empirical evidence suggests that combining the responses of several accurate and diverse classifiers can enhance the overall accuracy and reliability of a pattern classification system [4,10]. Despite reducing information to binary decisions, combining responses at the decision level, in the Receiver Operating Characteristic (ROC) space, allows to combine across a variety of classifiers trained with different hyperparameters, feature subsets and initializations.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, more and more applications require the integration of models and experts that come from different sources (human expert models, data mining or machine learning models, etc.). On the other hand, it has been shown that an appropriate combination of several models can give better results than any of the single models alone [26] [34], especially if the base classifiers are diverse [28].…”
Section: Introductionmentioning
confidence: 99%